Quantitative indicators model for universities activity quality assessment - Anikin, Igor; Lapteva, Svetlana; Bondarovskaya, Larisa; Tamer, Olga (International Journal of Psychosocial Rehabilitation, 2020)
The study examines the key sphere of higher education aimed at improving the quality and relevance of higher education; outlines which external quality assurance systems and major ratings currently exist in higher education, how these systems and rankings function, what consequences can be identified; critically compares quality guarantees and ratings; studies methodological approaches to the formation of an integrated system for assessing the achievement of target indicators of the university. Based on the analysis possible policy options regarding quality approaches are presented. An estimation model of the training activity based on the numerical index and a set of target indicators is presented.